Comparing the clinical acceptability of innovatedly made transpalatal arch (TPA) from 3D reconstructed model and conventionally-made TPA / Azanee-Nur Mohd Arif Fadzillah - Azanee-Nur, Mohd Arif Fadzillah (2019)
Introduction: Digital workflow have been widely implemented in dental clinics for easier data management and reduction of physical storage of dental records. However, the need for physical model supersedes the sophistication of virtual model in dental appliances fabrication. Thus, there is a need to investigate whether the 3D reconstructed model is clinically applicable for the construction of orthodontic appliances. Aim and objectives: The study aimed to investigate whether transpalatal arch (TPA) directly fabricated from 3D reconstructed model is a feasible alternative to conventionally constructed TPA for clinical practice, by assessing the patientsï¿½ oral health related quality of life (OHRQoL), pain level and cliniciansï¿½ preferences. Materials and methods: This is a two-part study comprising quantitative and qualitative methods. Part 1 comprised of a parallel group randomized clinical trial study on 52 subjects who were recruited from patients receiving orthodontic fixed appliances treatment at Faculty of Dentistry, University of Malaya. Twenty-six subjects were allocated into two groups each (CG and 3DG) by block randomization. TPAs (0.9mm stainless steel with midpalatal semi loop) were constructed on conventional stone model and 3D reconstructed model (ABS material printed by UP! Plus 3D Printer). Two outcomes were measured: (1) self?administered questionnaire of the modified short version of Malaysian Oral Health Impact Profile-14 (OHIP-14[M]) to assess the oral health related quality of life (OHRQoL). (2) self-administered pain level by visual analogue score. Data were collected at baseline (T0), and one week (T1), one month (T2) and three months (T3) iv after insertion of TPA. Part 2 is a qualitative study involving a Focus Group Discussion (FGD) among five clinicians who treated all the subjects to explore cliniciansï¿½ preference of clinical application. Result: All 52 subjects were analysed and there was no drop out in this study. Severity of OHRQoL among the patients was highest at first week insertion of TPA (10.08; S.D. 6.69) and improved after one month (8.37; S.D. 5.85) and three months (7.56; S.D. 4.97) of wear. There was no significant difference in OHRQoL between the two types of TPA (p>0.05) at all measured time points (T0, T1, T2 and T3). The most affected domain after wearing TPA was psychological discomfort and the least was social disability. There was no significant difference in pain level between the two types of TPA (p>0.05) at all measured time points (T1, T2 and T3). Four out of five clinicians preferred the TPA fabricated on 3D reconstructed model than the conventional TPA with three emerged themes (1) time factor, (2) molar band selection (3) cost factor. Conclusion: There was no significant difference of OHRQoL and pain level between the two types of TPA. Majority of clinicians preferred the TPA fabricated on 3D reconstructed model rather than the conventional TPA. The 3D reconstructed models are clinically acceptable as working models in replacing conventional stone models for TPA fabrication. Keywords: Transpalatal Arch (TPA), 3D printing, Oral Health Related Quality of Life (OHRQoL, orthodontic pain, focus group discussion (FGD)